This answer is restricted. Please login to view the answer of this question.

Login NowPythagorem theorem of two vectors states that if two vectors say \(\vec{u}\) and \(\vec{v}\) are orthogonal (i.e. their dot product us zero \(\vec{u} . \vec{v} = 0\) then

\(||\vec{u} + \vec{v}||^2 = ||\vec{u}||^2 + ||\vec{v}||^2\)

**Proof:**

\(||\vec{u} + \vec{v}||^2\)

\(= (\vec{u} + \vec{v}) (\vec{u} + \vec{v}) \)

\(= \vec{u}.\vec{u} + \vec{v}.\vec{v} + 2\vec{u}.\vec{v}\)

\(= \vec{u}.\vec{u} + \vec{v}.\vec{v} + 0\)

\(= ||\vec{u}||^2 + ||\vec{v}||^2\)

* proved*

Given

\(\vec{u}\) = (1, -1) and \(\vec{v}\) = (1, 1)

\(\vec{u} + \vec{v}\) = (1 + 1, -1 + 1) = (2, 0)

\(||\vec{u} + \vec{v}||^2\) = \((\sqrt{(2)^2 + 0})^2\) = 4

Also,

\(||\vec{u}||^2\) = \((\sqrt{(1)^2 + (-1)^2})^2\) = 2

\(||\vec{v}||^2\) = \((\sqrt{(1)^2 + (1)^2})^2\) = 2

\(||\vec{u}||^2 + ||\vec{v}||^2\) = 2 + 2 = 4 = \(||\vec{u} + \vec{v}||^2\)

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion